Modernization of cancer services in Moscow, the main challenges and possible solutions - A. P. Gnatyuk (Исследования и практика в медицине)
Malignant neoplasms are taking second place in the structure of mortality and continue to be a major public health problem, both in the Russian Federation and in Moscow. The relevance of medical care to patients with malignant neoplasms is determined by their social significance, as well as the complexity of detection and treatment, the continuing increase in the incidence. The aim of the Department of health and Oncology service of the city is to solve this problem.